Maize bran feruloylated oligosaccharides inhibited AGEs formation in glucose/amino acids and glucose/BSA models. (August 2019) - Huang, Junqing; Ren, Jiayi; Tao, Gabriel; Chen, Yongsheng; Yao, Shengwen; Han, Duoduo; Qiu, Ruixia
Abstract: Various Maillard reaction systems were established to investigate the effect of maize bran feruloylated oligosaccharides (FOs) on the formation of both endogenous and exogenous advanced glycation end-products (AGEs) under different pH values. The formation of AGEs and four kinds of dicarbonyl compounds (glyoxal, methylglyoxal, 3-deoxyglucosulose, 2, 3-butanedione) were determined by fluorescence spectrophotometry and HPLC, respectively. Results showed that maize bran FOs effectively inhibited the production of fluorescent AGEs. Moreover, increase in pH, temperature and concentration of FOs in reaction systems elevated the inhibition effects of feruloylated oligosaccharides, fluorescent AGEs and dicarbonyl compounds. Mainly because of the ester bond of FOs at high pH and/or temperature systems are readily to be hydrolyzed, resulting in the release of ferulic acid. Graphical abstract: Unlabelled Image Highlights: FOs inhibit the production of both endogenous and exogenous AGEs. Increase in pH, temperature and concentration elevate the inhibition effects. FOs can inhibit the oxidation of adducts. FOs can inhibit the adduction between protein and dicarbonyl compounds. FOs can inhibit the formation of dicarbonyl compounds.